Direct analysis of traditional Chinese medicines using surface‐enhanced raman scattering (SERS). Issue 10 (12th February 2014) - Zhao, Jing; Liu, Yang; Fales, Andrew M.; Register, Janna; Yuan, Hsiangkuo; Vo‐Dinh, Tuan
<x xml:space="preserve">Abstract</x> Surface‐Enhanced Raman Scattering (SERS) spectrometry provides an excellent tool to characterize chemical constituents in Traditional Chinese Medicines (TCMs) without requiring separation and extraction procedures. This study involved the use of SERS to analyze two TCMs, namely Coptis chinensis and Phellodendron amurense, and their main active constituent, berberine. Using silver nanospheres as SERS‐active probes, the decoctions of two raw TCMs and their counterfeits were analyzed. Density functional theory (DFT) was used to calculate the expected Raman spectrum of berberine, and liquid chromatography‐ mass spectrometry (LC‐MS) was used as a comparative technique to quantify the amount of berberine in the samples. The results of the SERS measurements were consistent with the results of DFT calculations and LCMS analyses. To our knowledge, this is the first time that the potential of SERS was demonstrated as a sensitive, rapid, and non‐destructive method to qualitatively and quantitatively analyze the active constituents in raw TCM products. Copyright © 2014 John Wiley & Sons, Ltd.